National Trends in the Prevalence of Diabetic Peripheral Neuropathy Among Diabetes Mellitus Patients in Indonesia (2010–2024): A Pooled Meta-Analysis of 46 Studies with 2,808 Participants - Susanti, Indah; Maria Seraph, Nero; Natasya Edward, Marry; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2025)
Background: Diabetic peripheral neuropathy (DPN) is a prevalent and debilitating complication of diabetes mellitus that significantly impacts quality of life and increases morbidity. Indonesia faces a rapidly growing diabetes burden; however, national-level estimates of DPN prevalence remain limited. Understanding the epidemiological patterns of DPN is critical to guide screening strategies, clinical management, and region-specific health interventions. Purpose: This study estimated, on a national basis, the prevalence of DPN among diabetic patients in Indonesia during the period 2010 to 2024. Methods: A meta-analysis was conducted using data sources and a comprehensive search of PubMed, Embase, Scopus, Web of Science, CINAHL Plus, and Google Scholar for relevant articles up to January 2025. A generalized mixed model was employed to analyze the pooled prevalence under the assumption of random effects. The risk of bias was assessed using the Newcastle-Ottawa Scale (NOS), and Heterogeneity was assessed through I² statistics and Cochran's Q tests. Results: The sample comprised 46 studies with 2808 participants. The prevalence of DPN was 76.65% (95% CI 64.82-85.40) based on the Random Effects Model. High prevalence was found in patients aged 40-60 with type 2 diabetes in institutional settings and moderate diabetes duration. Conclusion: The preponderance of DPN in Indonesia is tremendously high and differs across regions and demographics. Early detection and resources in situ are important for proper management. PROSPERO registration number: CRD42025643949